2021
DOI: 10.3390/microorganisms9030501
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Communities and Enzymatic Activities in Sediments of Long-Term Fish and Crab Aquaculture Ponds

Abstract: Aquaculture is among the most important and fastest growing agriculture sectors worldwide; however, it generates environmental impacts by introducing nutrient accumulations in ponds, which are possibly different and further result in complex biological processes in the sediments based on diverse farming practices. In this study, we investigated the effects of long-term farming practices of representative aquatic animals dominated by grass carp (GC, Ctenopharyngodon idella) or Chinese mitten crab (CMC, Eriochei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 39 publications
(50 reference statements)
1
14
0
Order By: Relevance
“…In the studied black carp polyculture ponds, the Shannon and Simpson diversity indices for aquatic bacteria increased during the mid-culture period (June, July, and August) in BP (p < 0.05), indicating that the bacterial diversity was in a dynamic succession process; the diversity decreased during the late culture period. The results were in accordance with those of a previous study [21], and the decreased species diversity in pond water may be due to the lesser nutrient availability in the late culture period.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the studied black carp polyculture ponds, the Shannon and Simpson diversity indices for aquatic bacteria increased during the mid-culture period (June, July, and August) in BP (p < 0.05), indicating that the bacterial diversity was in a dynamic succession process; the diversity decreased during the late culture period. The results were in accordance with those of a previous study [21], and the decreased species diversity in pond water may be due to the lesser nutrient availability in the late culture period.…”
Section: Discussionsupporting
confidence: 92%
“…As the main production mode, the traditional pond polyculture system is a common practice in aquaculture [20]. It was reported that the high nutrient accumulation and low transfer ratio of nutrient output in ponds caused diverse biological activities in the water and sediments [20][21][22]. The present study demonstrated dynamic changes in water microbial composition and the driving environmental factors during a culture period in black carp polyculture ponds, a popular aquaculture mode in South China.…”
Section: Discussionmentioning
confidence: 51%
“…Microbial communities play a pivotal role in energy and matter cycles in the sea, and the stability of the micro-ecological environment is a prerequisite for the aquaculture fish health (Olafsen, 2001;Vadstein et al, 2018). Previous studies mainly focused on the bacterial community compositions of aquaculture environments in pond ecosystems (Zhao et al, 2020;Zhang et al, 2021;Zeng et al, 2021). However, microbial communities in the open-oceanic mariculture ecosystems are understudied compared to the pond environment microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the sediment could become highly reduced during the culture periods with the decomposition of organic matter, and cause significant effects on the nitrification process ( Dai et al, 2018 ). Although effects of environmental characteristics on microbial community variation have been found during disturbance ( Guggenheim et al, 2020 ; Monteiro et al, 2020 ), different responses of microbial communities to environmental change due to adaption has also been detected ( Dai et al, 2018 ; Xia et al, 2020 ; Zhang et al, 2021 ). In addition, research on agricultural cropland has indicated a significant influence of stochastic processes besides deterministic processes on bacterial community assembly ( Barnett et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%